2017
DOI: 10.1063/1.4996242
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient solid state magnetoelectric gyrators

Abstract: An enhancement in the power-conversion-efficiency (η) of a magneto-electric (ME) gyrator has been found by the use of Mn-substituted nickel zinc ferrite. A trilayer gyrator of Mn-doped Ni0.8Zn0.2Fe2O3 and Pb(Zr,Ti)O3 has η = 85% at low power conditions (∼20 mW/in3) and η ≥ 80% at high power conditions (∼5 W/in3). It works close to fundamental electromechanical resonance in both direct and converse modes. The value of η is by far the highest reported so far, which is due to the high mechanical quality factor (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…Recently, the progress made in the field of magnetoelectric (ME) laminate composites allows potential high performance applications such as magnetic field sensors [2][3][4][5], current sensors [6][7][8][9][10][11][12][13][14][15][16], gyrators [17], filters [18] and more recently, memory devices [19][20][21][22][23]. In the field of current sensors, magnetoelectric composites show many advantages : (i) high performances, (ii) low cost, (iii) power supply free, (iv) galvanic isolation and (v) simplified electronic circuits [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the progress made in the field of magnetoelectric (ME) laminate composites allows potential high performance applications such as magnetic field sensors [2][3][4][5], current sensors [6][7][8][9][10][11][12][13][14][15][16], gyrators [17], filters [18] and more recently, memory devices [19][20][21][22][23]. In the field of current sensors, magnetoelectric composites show many advantages : (i) high performances, (ii) low cost, (iii) power supply free, (iv) galvanic isolation and (v) simplified electronic circuits [24].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the thickness ratio between two ferromagnetic phases (nickel‐zinc ferrite and Metglas) plays an important role towards power efficiency working under H Bias = 0 or higher optimal magnetic bias. Under resonance, the maximum power efficiency ( η max ) was dependent on Q m , given as: ηmax=11+2ωsR1×φm2φp2 where R1=Rmφm2 is the equivalent resistance; Rm=πZ08Qm is the mechanical resistance; Z0=trueρv¯Alam is the impedance; ωs=1LmCm is the angular frequency when the ME gyrator is operated under resonance; φm=2Amd33,m s33H and φp=wd31,p s11E are the magneto‐elastic and elasto‐electric coupling factors, respectively. Figure shows the dependence of the power efficiency ( η ) on the number of Metglas foils ( n ).…”
mentioning
confidence: 99%
“…For ME gyrators that have a design similar to ME transformers, it was shown that, by optimizing the size and parameters of the composite structure, it is possible to increase the power transfer efficiency up to η ≈ 90% [26][27][28][29]. One can hope that similar increase in the power transfer efficiency can be realized for the ME transformers as well.…”
Section: Ways To Improve Characteristics Of the Magnetoelectric Transmentioning
confidence: 99%